Evaluation of metals and hydrocarbons in sediments from a tropical tidal flat estuary of Southern Brazil. Issue 1 (15th March 2015) - Costa, Eduardo S.; Grilo, Caroline F.; Wolff, George A.; Thompson, Anu; Figueira, Rubens Cesar Lopes; Neto, Renato Rodrigues
Highlights: Metals and hydrocarbons in estuary mouth showed indication of anthropogenic input. Metals in estuary mouth were associated with petroleum-derivative hydrocarbons. Metals were possibly associated with activities that use oil and its derivatives. Copper was associated with domestic sewage. Abstract: Although the Passagem Channel estuary, Espírito Santo State, Brazil, is located in an urbanized and industrialized region, it has a large mangrove system. Here we examined natural and anthropogenic inputs that may influence trace metal (Cd, Cr, Cu, Ni, Sc, Pb and Zn) and hydrocarbon ( n -alkane and terpane) deposition in three sediment cores collected in the tidal flat zone of the estuary. The cores were also analyzed for carbonate, grain size and stable isotopic composition (δ 13 Corg. and δ 15 Ntotal ). Metal enrichment and its association to petroleum hydrocarbons in the surficial sediments of one of the cores, indicate crude oil and derivative inputs, possibly from small vessels and road run-off from local heavy automobile traffic. At the landward sites, the major contributions for metals and hydrocarbons are from natural sources, but in one case, Cu may have been enriched by domestic effluent inputs.